Agricultural intensification: Who intensifies and how does it contribute to income growth? - Berhane, Guush; Abate, Gashaw T.; Wolle, Abdulazize (International Association of Agricultural Economists, 2021)
Ethiopia has made substantial efforts in the last three decades to increase agricultural productivity through modern input intensification and stimulate overall economic growth. Important progresses have been registered in terms of overall economic growth and agriculture has been the main driver of growth. Despite the high growth rates in recent decade, Ethiopia’s overall intensification and yield levels remained low. This study examines the trends and drivers of agricultural intensification and productivity growth during the recent decade using three rounds of household data collected from the four agriculturally largest regions of the country. The main analysis on the relationship between input intensification, yield, and household welfare employs a recent variant of the correlated random effect model to address the time-invariant unobserved heterogeneity and a control function to mitigate time-varying unobserved heterogeneity. The descriptive results indicate a positive trend in both the adoption rate and intensity of inputs and output, albeit from a low base and with considerable heterogeneity by access to information, rainfall variability, labor, soil quality, remoteness, among others. The econometric results show significant association between intensification, yield growth, and household dietary diversity (a proxy measure for food and nutrition security). However, the current yield level is not significantly associated with household durable assets and per capita consumption expenditures. Additional welfare improving productivity gains through increased input intensifications may require investments to put in place appropriate fertilizer blends linked with localized soil nutrient requirements, investments to generate locally suited improved seeds and appropriate mechanisms to reach farmers, ways to mitigate rainfall risk, and investments to remodel Ethiopia’s extension system to provided much needed technical support to farmers on production methods.